Combination of clopidogrel and everolimus completely abolished the development of transplant arteriosclerosis - Eckl, S.; Heim, Christian; Abele-Ohl, S.; Hoffmann, J.; Weyand, M.; Ensminger, S. M.; Weyand, Michael (Transplantationsmedizin, 2009)
Introduction: Our group has previously shown that platelet inhibition with clopidogrel reduced the formation of transplant arteriosclerosis (TxA). The aim of this study was to investigate whether a combination of cyclosporine or everolimus with clopidogrel has a beneficial effect on the development of TxA. Methods: Fully allogeneic C57BL/6 (H2b) donor aortas were transplanted into CBA (H2k) recipients. Recipient mice were treated with cyclosporine (2mg/kg/d) and everolimus (0,05mg/kg/d) alone or in combination with clopidogrel (1mg/kg/d). Grafts were analysed by histology and morphometry on day 30 after transplantation. Results: In mice treated with clopidogrel alone, TxA was reduced as compared to untreated controls (intima proliferation 57%+/-13% vs. 79%+/-8% [control]/n=5). Daily application of everolimus significantly reduced the development of TxA compared to untreated controls (intima proliferation of 27% +/- 10% vs. 79% +/-8% [control], n=5). Strikingly, combination of clopidogrel and everolimus almost completely abolished the formation of TxA (intima proliferation: 14% +/- 10% vs. 79% +/- 8% [control], n = 5). In contrast, daily application of cyclosporine alone did not reduce the development of TxA compared to controls (intima proliferation: 74% +/- 7% vs. 79% +/- 8% [control], n=5). In addition combination of cyclosporine and clopidogrel compared with clopidogrel alone showed no additive effect. Conclusion: These results demonstrate that combination of clopidogrel and everolimus can completely abolish the development of TxA in a mouse aortic allograft model. Our findings have also important clinical implications as patients suffering from TxA after cardiac transplantation may benefit from treatment with a combination of these drugs.
CRIS-Team Scopus Importer:2024-06-04